The relationship of motivational values of math and reading teachers to student test score gains - Loewen, David Allen (Kansas State University, 2013)
This exploratory correlational study seeks to answer the question of whether a relationship exists between student average test score gains on state exams and teachers’ rating of values on the Schwartz Values Survey. Eighty-seven randomly selected Kansas teachers of math and/or reading, grades four through eight, participated. Student test score gains were paired with teachers and averaged. The results of these backward stepwise entries of multiple regressions using SPSS software are reported. Significant relationships with large effect sizes are reported for teacher values and student test score gains in reading and math. Models of teacher values are found that account for thirty-two percent of the average student test score gains in reading and for forty-three percent of the average student test score gains in mathematics. The significant model of values with the greatest adjusted relationship with reading test score gains is described as the Relational Teacher Value Type. The valuing of True Friendship (close supportive friends) and the valuing of Sense of Belonging (feeling that others care about me) proved to be the most powerful indicators of student reading score gains within this type. The significant model of values with the greatest adjusted relationship with mathematics test score gains is described as the Well-Being Teacher Value Type. The valuing of Healthy (not being sick physically or mentally), the valuing of Reciprocation of Favors (avoidance of indebtedness), and Self Respect (belief in one’s own worth) proved to be the most powerful indicators of student mathematics test score gains within this type. The significant value items within each of the above types’ models are discussed regarding possible reasons for their relationships to student test score gains. A value that is found significant for both reading and mathematics teachers in accounting for student test score gains is Moderate (avoiding extremes of feeling and action). Of the teachers in the study that taught mathematics and reading, their students’ mathematics score gains did not correlate in a statistically significant way with their students’ reading score gains, suggesting that a teacher’s ability to teach math has little to do with a teacher’s ability to teach reading.
Keywords: Teacher; Values; Learning; Value-added; Correlation; Effectiveness; Education, General (0515); Language Arts (0279); Mathematics Education (0280)